Latin America seen by the Moroccan press: The case of the newspaper Al-Ittihad Al-Ichtiraki - HIRI, Abdelhak (2021)
This research claims to reveal the image of Latin America in the Moroccan press, specifically in the newspaper Al Ittihad Al Ichtraki. The main purpose of this research is to investigate the associated representation of Latin America of this press by using different methods such as qualitative, thematic, and stylistic. The main objective can be defined as to explain motivations that make the press to lead that representation. The second objective of this study, related to the first, is to study the position of this information. Therefore, during this research analyzing methodology has been used to qualitificate, measure and accomplish by conclusions.